Sistem Pemberian Air Dan Pupuk Pada Tanaman Melon Menggunakan Irigasi Tetes - Ella Alfareza; Tati Erlina (CHIPSET, 2023)
Melon is one of the high value crops, so it needs to be empowered. Melon growth is closely related to the state of water, soil pH, and nutrients. A mismatch in water content causes stunted growth. Melon grow well in soil with a pH of 6-7, where nutrients are easily absorbed. Human has limitations in watering, fertilising and controlling the pH of the soil manually. Therefore, a system for automatic watering, fertilisation and pH control with drip irrigation is needed. This system uses Arduino Mega2560 as a microcontroller, RTC for scheduling watering and fertiliser, pH sensor for controlling soil pH, water level sensor to measure the contents of the container with notification to Telegram. In this research, the system succeeded in watering and fertilising on schedule with 100% time accuracy, and controlling soil pH with a pH measurement accuracy of 95.57%. The system also successfully detected the solution running out and sent the notification to Telegram. The melon plants grow faster using the system than manually, with a difference in plant height of 1.029 cm on day 7. Thus it can be concluded that the system for automatic watering, fertilising, and pH control of melon plants has been successfully built.